2019
DOI: 10.15171/icnj.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Acceptance and Commitment Therapy on Anxiety, Depression, and Stress in Patients with Spinal Cord Injuries

Abstract: Background: Since the number of patients with spinal cord injuries is increasing, paying attention to these patients' psychological problems is a priority. This study aimed to evaluate the effect of acceptance and commitment therapy on anxiety, depression, and stress in patients with spinal cord injuries. Methods: The present study had utilized a single-subject approach in the form of multiple baseline design. The samples were selected using purposive sampling based on convenience sampling method. The statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The findings of this study support those of Hatefi et al ( 2019 ), who found that emotional stress for people who have experienced injuries is common. These findings are also supported by Torabian, Sabet and Meschi ( 2019 ), who observed that patients who have sustained an SCI often become emotionally weak and have traumatic depression, leading to suicidal thoughts if not managed properly in the rehabilitation process.…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 67%
“…The findings of this study support those of Hatefi et al ( 2019 ), who found that emotional stress for people who have experienced injuries is common. These findings are also supported by Torabian, Sabet and Meschi ( 2019 ), who observed that patients who have sustained an SCI often become emotionally weak and have traumatic depression, leading to suicidal thoughts if not managed properly in the rehabilitation process.…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 67%
“…The patients learn that avoidance may relieve a person of stress in the short term but worsens the problem in the long run and has a more negative impact, which is one of the primary mechanisms to improve the quality of life of these people [10]. Also, in the present study, components such as awareness of thoughts, behavior, emotions, and feelings were addressed, which play an essential role in dealing with and interpreting situations and problems [26]. ACT characteristics, such as being aware of thoughts, behaviors, emotions, and feelings, warn people against performing automatic behaviors and reactions and paying too much attention to internal experiences.…”
Section: Discussionmentioning
confidence: 90%
“…The purpose of acceptance is for the individual to accept all the inner experiences offered, that is, thoughts, feelings, memories, and bodily feelings without the need to defend against them. 14,22 This study had some limitations. The first was the small sample size.…”
Section: Discussionmentioning
confidence: 96%